A Civil Society The Public Space of Freemason Women in France, 1744-1944. - ALLEN, JAMES SMITH (Book collections on Project MUSE., 2022)
James Smith Allen explores the two-hundred-year struggle to initiate women as full participants in the masonic brotherhood that shared in the rise of France's civil society and its "civic morality" on behalf of women's rights.